Assessing Mitral Valve Area and Orifice Geometry in Calcific Mitral Stenosis: A New Solution by Real-Time Three-Dimensional Echocardiography - Chu, John W. (2008)
BACKGROUND: Planimetry of mitral valve area (MVA) is difficult in calcific mitral stenosis (CaMS) in which limiting orifice is near the annulus, and unlike rheumatic mitral stenosis (RhMS), does not present an area for planimetry at the leaflet tips. Moreover, pressure half time (PHT)-derived MVA (MVA(PHT)) has limitations in patients with CaMS in whom there are coexisting conditions that affect LV chamber compliance. We tested the hypothesis that real-time 3-dimensional echocardiography (RT3D) can guide measurement at the narrowest orifice in CaMS. METHODS: In 34 patients with CaMS, MVA by RT3D (MVA(RT3D)) was obtained using a color-defined planimetry technique performed “en face” at the smallest annular orifice cross-section (diastolic maximum). MVA(RT3D) and MVA(PHT) were compared with an independent standard: MVA by continuity equation (MVA(CEQ)). In a subgroup of 10 patients with CaMS or RhMS, the 3-dimensional shape of the stenotic mitral valve was examined, guided by color flow mapping. RESULTS: MVA(PHT) overestimated the mitral orifice area compared with MVA(CEQ) (2.01 ± 0.52 cm(2) vs 1.75 ± 0.46 cm(2); P = .037), whereas there was no significant difference in MVA(RT3D) and MVA(CEQ) (1.83 ± 0.52 cm(2) vs 1.75 ± 0.46 cm(2), respectively, P = .61). MVA(RT3D) had a greater correlation with MVA (CEQ) than MVA(PHT) (R = 0.86 vs 0.59 MVA(RT3D) vs MVA(PHT), respectively). There was better agreement between MVA by RT3D and MVA by continuity equation than MVA by PHT and MVA by continuity equation (difference in MVA: 0.23 ± 0.15 cm(2) vs 0.43 ± 0.29 cm(2); P < .0001, MVA(RT3D) − MVA(CEQ) vs MVA(PHT) − MVA(CEQ), respectively). In CaMS, there was a tubular geometry to the valve shape. In contrast, RhMS had a doming funnel-shaped geometry. CONCLUSION: RT3D provides an accurate measurement of MVA in CaMS. In contrast with the doming valve shape present in RhMS, the limiting anatomic orifice area occurs at the annulus in CaMS as measured by RT3D and reflects the effective orifice area as present in a tubular valve geometry.